PROFIL PEMECAHAN MASALAH SISWA KELAS IX SMP NEGERI 2 PALU DALAM MENYELESAIKAN MASALAH MATERI UNTUNG DAN RUGI BERDASARKAN SELF-EFFICACY - Annisa Annisa; I Nyoman Murdiana; Tegoeh S. Karniman (Universitas Tadulako, 2025)
This study aims to describe the problem-solving profile of grade IX students of SMP Negeri 2 Palu in solving profit and loss material problems based on their self-efficacy levels. The research approach used is descriptive qualitative, with research subjects consisting of two students, each with a high and low level of self-efficacy. Data were collected through self-efficacy questionnaires, written tests, and interviews, which were analyzed using the Miles and Huberman model. The results showed that students with high levels of self-efficacy were able to complete each stage of problem solving based on Polya's steps well, starting from understanding the problem, planning problem solving, implementing the plan, to re-checking the results. High self-efficacy students showed confidence and accuracy in identifying information, designing solutions, and performing calculations. In contrast, students with low self-efficacy were only able to understand part of the information, often made mistakes in calculations, and did not re-check the answers because they lacked confidence. The self-efficacy factor has been shown to influence students' ability to solve mathematical problems.